Acoustics: Sound Fields, Transducers and Vibration - Beranek, Leo L. 1914-2016; Mellow, Tim J. (Elsevier, AP, Academic Press, 2019)
Acoustics: Sound Fields, Transducers and Vibration, Second Edition guides readers through the basics of sound fields, the laws governing sound generation, radiation, and propagation, and general terminology. Specific sections cover microphones (electromagnetic, electrostatic, and ribbon), earphones, and horns, loudspeaker enclosures, baffles and transmission lines, miniature applications (e.g. MEMS microphones and micro speakers in tablets and smart phones), sound in enclosures of all sizes, such as school rooms, offices, auditoriums and living rooms, and fluid-structure interaction. Numerical examples and summary charts are given throughout the text to make the material easily applicable to practical design.New to this edition:- A chapter on electrostatic loudspeakers - A chapter on vibrating surfaces (membranes, plates, and shells)Readers will find this to be a valuable resource for experimenters, acoustical consultants, and to those who anticipate being engineering designers of audio equipment. It will serve as both a text for students in engineering departments and as a valuable reference for practicing engineers.- Provides detailed acoustic fundamentals, enabling better understanding of complex design parameters, measurement methods and data- Extensive appendices cover frequency-response shapes for loudspeakers, mathematical formulas and conversion factors